Ocena przydatności tradycyjnych systemów rachunku kosztów do celów zarządczych w zakładzie opieki zdrowotnej - Trojnacka, Mirosława (Evaluation of usefulness of the traditional cost accounting systems for management aims in health care institutions, 2008)
The traditional cost accounting applied in health care institutions is assigned to medical service based on the value of provided services. The participation of indirect in the complete costs becomes to be more significant, and traditional cost accounting provides less important and accurate information about isolated costs of treatment. The traditional cost accounting is usually not enough for management decision process. Therefore, to avoid estimating errors as a result of assumption that all costs should be paid on medical services - in fact they are paid almost every time, when the following service is made - there is a need for an application of the activity based costing in health care institutions.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 435-445